Adventures in Organophosphorus Chemistry - Dulaney, James W. (My University, 2015)
Organophosphorus compounds have been an increasingly important part of organic synthesis since the discovery of the Arbuzov rearrangement in 1905. In the century that followed this discovery, the applications of phosphorus-based reagents in synthesis has grown to incorporate the Wittig and Horner-Wadsworth-Emmons reactions for alkene formation, as well as the Mitsunobu inversion reaction, which is used to convert alcohols to a wide range of products with inversion of configuration.
Color poster with text and chemical models.
Keywords: Mitsunobu reaction; Organophosphorus; Esters; Green reactions; Green chemistry; Posters